SPAS Book Series, Collection A - Statistics and Probability African Society, The (Statistics and Probability African Society, The, 2018)
SPAS EDITIONS is a collection of monographs and edited books published by the Statistics and Probability African Society (SPAS). Expected sub-series include: SPAS Textbooks, SPAS Research Monographs, and SPAS Books.
Keywords: Electronic journals